1961
DOI: 10.1515/hfsg.1961.15.2.44
|View full text |Cite
|
Sign up to set email alerts
|

Über Entstehung und Aufbau von Reaktionsholzzellen - 2. Mitt.: Morphologie der Druckholzzellen vonTaxus baccataL.

Abstract: 44W. Wergin und G. Casperscn Holzforschung diameters according to Warren. The results on cellulose II micelles and wood fibers were in good qualitative agreement with those obtained by other methods. Also, reasonable surface values were ascertained for a lignin and a sample of groundwood fines, two substances whose surfaces were hitherto not easily accessible. Apparently the method holds good promise for'a variety of organic specimens with colloidal structure features.Zusammenfassung Eine einfache Röntgenflach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In this connection it is interesting that in compression wood where the S3 layer is absent or only feebly developed (WARDROP & DADSWELL 1950), WERGIN & CASPERSON (1961) found thickenings which they concluded to be part of the S2-layer. These helices, however, run in the same S direction as do the S3 spirals in normal tracheids.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this connection it is interesting that in compression wood where the S3 layer is absent or only feebly developed (WARDROP & DADSWELL 1950), WERGIN & CASPERSON (1961) found thickenings which they concluded to be part of the S2-layer. These helices, however, run in the same S direction as do the S3 spirals in normal tracheids.…”
Section: Discussionmentioning
confidence: 97%
“…In all the above genera they characterize the tracheids, though in the latter they may be absent in the outer portion of the late wood of the growth ring (ANONY-MOUS 1925). A special study of the spirals has been made for Taxus by WERGIN & CASPERSON (1961) and WARDROP & DAVIES (unpublished) and for Pseudo-tsuga by LIESE & HARTMANN-FAHNENBROCK (1953), COTE (1967), HODGE & WARDROP (1950). WARDROP (1964) gave information about both genera.…”
Section: Introductionmentioning
confidence: 99%
“…Within the ribs, the lamellae parallel the wall surface (WERGIN and CASPERSON, 1961;WARDROP and DAVIES, 1964). Within the ribs, the lamellae parallel the wall surface (WERGIN and CASPERSON, 1961;WARDROP and DAVIES, 1964).…”
Section: Compression Woodmentioning
confidence: 99%
“…Frey-Wyssling (1959), Wardrop (1964), and Wardrop and Dadswell (1951) have contended that helical thickenings are very loosely attached to the inside layer of the normal 00007-1048/78/0700-0139 $02.00© 1978 Blackwell Scientific Publications secondary wall and are overlaid at a slightly different angle to the orientation ofthe microfibrils in it. Casperson (1965) and Wergin and Casperson(1961), on the other hand, suggested that helical thickenings are an integral part of the secondary wall. Preston (1974) has regarded them as homologous with the other layers of the secondary wall and suggests that they could represent an attempt to continue secondary wall formation at a time when the life of the cell is growing to its close.…”
Section: Introductionmentioning
confidence: 99%